2006
DOI: 10.1136/adc.2005.092007
|View full text |Cite
|
Sign up to set email alerts
|

Improving child protection: a systematic review of training and procedural interventions

Abstract: Current evidence supports the use of procedural changes that improve the documentation of suspected child maltreatment and that enhance professional awareness. The lack of an evidence based approach to the implementation of child protection training may restrict the ability of all health professionals to fulfil their role in the child protection process. Formal evaluation of a variety of models for the delivery of this training is urgently needed with subsequent dissemination of results that highlight those fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 23 publications
0
57
0
1
Order By: Relevance
“…A recent critical review of simulation-based medical education research (SBME) observed that research into SBME has matured over the past 40 years and, given the impact and educational utility of such research, will likely increase in the future. Consistent with reviews of evaluations of training in child welfare (Carter et al, 2006;Collins et al, 2010) stronger research designs, recognition of the complexity of evaluating effectiveness, and integration with organization teaching contexts is recommended (McGaghie et al, 2010). Recent studies in social work on the use of simulation-based training demonstrates positive student learning outcomes in generic social work skills (Bogo et al, 2012;Logie et al, 2013;Rawlings, 2012) and in cultural competence (Lu et al, 2011).…”
Section: Training In Child Welfarementioning
confidence: 80%
See 1 more Smart Citation
“…A recent critical review of simulation-based medical education research (SBME) observed that research into SBME has matured over the past 40 years and, given the impact and educational utility of such research, will likely increase in the future. Consistent with reviews of evaluations of training in child welfare (Carter et al, 2006;Collins et al, 2010) stronger research designs, recognition of the complexity of evaluating effectiveness, and integration with organization teaching contexts is recommended (McGaghie et al, 2010). Recent studies in social work on the use of simulation-based training demonstrates positive student learning outcomes in generic social work skills (Bogo et al, 2012;Logie et al, 2013;Rawlings, 2012) and in cultural competence (Lu et al, 2011).…”
Section: Training In Child Welfarementioning
confidence: 80%
“…Training designs varied in length, from 6 hours to 3 months, and in their design, including classroom training and supervision, didactic teaching and role play, video feedback, and use of the internet. Carter et al (2006) conducted a systematic review of training and procedural interventions to improve identification and management of child maltreatment by health professionals. They also found variation in length, from a few hours to several days, and in design, including didactic, computer assisted learning, and interactive strategies with audiotapes, written feedback on case notes, action research, focus groups, and videoconferencing consultation on assessment of clinicians' current cases.…”
Section: Training In Child Welfarementioning
confidence: 99%
“…Half of EMTs in a national sample requested additional training about the signs and symptoms of child maltreatment, and only 25% strongly agreed that they felt comfortable reporting physical abuse; fewer felt comfortable reporting sexual abuse (9.2%) or neglect (21.0%) [15]. Effective training, policies, and practices that improve reporting rates already exist [25,26]. For example, use of a structured screening tool in hospital emergency departments can increase the identification of child maltreatment [27].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of training concerned with improving child protection (Carter et al, 2006) found only seven papers which assessed outcomes, all of which were pre-/postresearch designs. Five of these were of single agency training, all involving doctors or nurses, and two were interprofessional.…”
Section: The Outcomes Of Interprofessional and Interagency Trainingmentioning
confidence: 99%